PENGARUH RETURN ON ASSET, RETURN ON EQUITY , CURRENT RATIO, UKURAN PERUSAHAAN, NET PROFIT MARGIN, DAN DEBT EQUITY RATIO TERHADAP KEBIJAKAN DEVIDEN (Studi Kasus Perusahaan sektor Manufaktur yang terdaftar di Bursa efek indonesia Periode 2014 - 2016) - Rajaza Deva Prabowo, 15.05.52.0331; Wahyudi, Djoko (Students' Journal of Accounting and Banking, 2019)
The purpose of this study was to analyze the influence of return on asset, return on equity, current ratio, firm size, net profit margin, and debt to equity ratio on dividend policy. The population of this research is manufacturing companies listed in Indonesia Stock Exchange (BEI) in 2014-2016. The type of data used is secondary data by using the method of data collection documentation. The analytical method in use is the multiple regression analysis. The results showed that the return on equity, current ratio, firm size was significant positive effect on dividend policy. Debt to equity was significant negative on dividend policy. Return on asset and return on equity was not significantly positive effect on dividend policy.